Managing faculty's work-life balance in Indian business schools - Nayak, Parameshwar (Teorija in praksa, 2018)
This paper examines the impact of organisation, family and social support on how faculty members working in business schools in national capital region (NCR) of India manage their work-life balance. The study is based on a survey that mainly used quantitative methods to collect the primary data. The study sample consists of 482 faculty members who work in different business schools in NCR of India. Factor analysis, reliability, a t-test and Anova were used to determine the effect of organisation, family and social support on demographic variables. The findings reveal that male faculty members are better able to manage their work-life balance than their female counterparts. Family support plays an important role in times of stress. This paper will help business schools in India in updating their policies to provide better lives for their employees and ensure an improved work culture.
Keywords: College teachers; Delo in družina; Organizacijska kultura; Organizational culture; Visokošolski učitelji; Work and family